An efficient iterative algorithm for moving target positioning in distributed MIMO radars - Zhao, Hai-Ni; Dong, Chun-xi (2021 IEEE International Conference on Computer Science, Electronic Information Engineering and Intelligent Control Technology (CEI), 2021)
This paper proposes an efficient iterative algorithm for determining the position and velocity of a moving target in di stributed MIMO radar systems. We first formulate the localizatio n problem as a constrained weighted least squares (CWLS) probl em, which is essentially a quadratically constrained quadratic pro gramming (QCQP) problem due to its quadratic equality constrai nts. Then, the QCQP problem is transformed into a linearly const rained quadratic programming (LCQP) problem through approx imating each non-convex constraint as a linear constraint, and it i s solved iteratively based on QR decomposition. The closed-form solution in each iteration for solving the LQCP problem makes th e proposed method have high computational efficiency. The perfo rmance of the proposed method is validated via numerical simulations.